Long-term safety and efficacy study of a medical device containing xyloglucan, pea protein reticulated with tannins and xylo-oligosaccharides, in patients with diarrhoea-predominant irritable bowel syndrome. (May 2021) - de los Rios, Constanza Ciriza; Falcón, Blanca Serrano; Arguelles-Arias, Federico; Pérez, Esperanza; Teruel, Carlos; Geijo, Fernando; Rey, Enrique
Background: Irritable bowel syndrome with diarrhoea (IBS-D) is a frequent problem associated with a significant socioeconomic implication. Increased gut permeability is an important pathophysiological mechanism. A medical device containing xyloglucan (XG), pea protein and tannins (PPT) from grape-seed extract, and xylo-oligosaccharides (XOS) has proven restoration of intestinal barrier function. Our objective was to evaluate the efficacy and safety of treatment with the medical device XG + PPT + XOS (XG-PPT-XOS) in adult patients with IBS-D in a clinical setting for 6 months. Material and methods: This was a multicentre, open-label, prospective, observational study conducted to evaluate long-term safety and efficacy of XG-PPT-XOS. IBS-D adult patients (Rome IV criteria) were included and received two tablets twice daily for 6 months. IBS Symptom Severity Score (IBS-SSS) and bowel habit were registered at baseline and monthly, until the end of follow up. Efficacy was evaluated by comparison of mean scores at each time point. Results: 50 patients were included, of which 19 completed the 6 months. IBS-SSS score decreased from 312.2 ± 82.2 to 213.6 ± 109.9 ( p < 0.0001) at 1 month and 192.0 ± 108.9 at the last visit completed; diarrhoea score decreased from 45.6 ± 17.9 to 25.7 ± 17.7 and 25.3 ± 17.2 at 1 month and at the last visit completed, respectively. Pain score decreased from 107.8 ± 49.9 at baseline to 73.2 ± 57.3 ( p < 0.0001) at 1 month and bloating score from 56.4 ± 28.8 at baseline to 42.8 ± 32.6 ( p < 0.001) at 1 month, reaching 62.4 ± 56.0 and 40.4 ± 34.3, respectively, at the last visit completed. Adverse effects were mild and mostly not related to treatment. Conclusion: Treating IBS-D patients with XG-PPT-XOS is effective and safe in the long term within a clinical setting, improving all IBS-D symptoms from the first month of treatment and showing a sustained response over the term of therapy.